A Robust Image Watermarking Method based on Contourlet Transform for Correcting Geometric Attacks - M, Abhinaya; Umamakeswari, A (International Journal of Engineering and Technology, 2018)
A watermarking technique is proposed using Discrete Wavelet Transform (DWT), Discrete Cosine Transform (DCT), and Singular Value Decomposition (SVD) techniques to implement information hiding. Embedding can be done by dividing the host image into four rectangular segments which are non-overlapping called sub-images using hybrid scheme. Redundancy reduces cropping attack. The main aim is to reduce the effect of geometric bouts, such as rotation, translation, and affine translation using synchronization technique. Watermarks can be a binary random sequence of different lengths. Data replication and hamming code are two error modification methods utilized in the proposed scheme. Achieved results show comparable robustness against geometric attacks and signal processing. Contourlet transform can be used to improve the visual feature of the image. After embedding the image or data, contourlet transform is applied in the frequency domain to improve robustness. The optimal mapping function is obtained using contourlet transform which increases Peak Signal to Noise Ratio (PSNR) and hiding capacity with low distortion.Â Â